Planning for Immediate Loading of Implant-Supported Prostheses: Literature Review - Delben, Juliana Aparecida [UNESP]; Goiato, Marcelo Coelho [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Magro Filho, Osvaldo [UNESP] (Allen Press Inc, 2012)
The aim of this study was to present the factors that influence planning for immediate loading of implants through a literature review for treatment success. Research was conducted in the PubMed database including the key words immediate implant loading, implant-supported prostheses, and implant planning for studies published from 2000 to 2011. Forty-eight articles were used in this review to describe the indications and counterindications, presurgical planning, and technologies available for planning of this treatment alternative.
Keywords: dental implant; implant-supported prosthesis; immediate loading